2019
DOI: 10.3390/v11111070
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Omics Study of Chicken Infected by Nephropathogenic Infectious Bronchitis Virus

Abstract: Chicken gout resulting from nephropathogenic infectious bronchitis virus (NIBV) has become a serious kidney disease problem in chicken worldwide with alterations of the metabolic phenotypes in multiple metabolic pathways. To investigate the mechanisms in chicken responding to NIBV infection, we examined the global transcriptomic and metabolomic profiles of the chicken’s kidney using RNA-seq and GC–TOF/MS, respectively. Furthermore, we analyzed the alterations in cecal microorganism composition in chickens usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…Respiratory lesions, which are the most common pathogenic characteristic of IBV, subsequently recover and do not lead to the death of infected chickens [25,26]. Similar to QX-type strains, the renal lesions of urate deposition may be responsible for the death of chickens, although the mortality rate caused by TW I-type IBV was relatively low [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory lesions, which are the most common pathogenic characteristic of IBV, subsequently recover and do not lead to the death of infected chickens [25,26]. Similar to QX-type strains, the renal lesions of urate deposition may be responsible for the death of chickens, although the mortality rate caused by TW I-type IBV was relatively low [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the chicken model have shown compositional changes in gut microbiota and differences in some of immune gene expression levels following H9N2 avian influenza virus (AIV), Newcastle disease virus (NDV) or infectious bronchitis virus (IBV) infection [ 29 32 ]. However, there are many environmental factors, such as age, breed, diet, housing, hygiene, and temperature that can also affect chicken microbiota [ 33 , 34 ] and thus might change the interactions between the host and viruses during the time of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Such understanding can provide invaluable insights into molecular pathogenesis in birds and various pathways involved in virus-host interactions. Recent advances in genomics, transcriptomics, proteomics, and metabolomics are now often incorporated into methodologies to analyze cellular and molecular interactions in biological systems [ 17 ].…”
Section: Introductionmentioning
confidence: 99%